Changes of Blood Pressure, Renin, and Angiotensin after Bilateral Nephrectomy in Patients with Chronic Renal Failure. Issue 5842 (23rd December 1972) - Medina, A.; Bell, P. R. F.; Briggs, J. D.; Brown, J. J.; Fine, A.; Lever, A. F.; Morton, J. J.; Paton, A. M.; Robertson, J. I. S.; Tree, M.; Waite, M. A.; Weir, R.; et al.
Abstract : Circulating levels of renin, angiotensin I, and angiotensin II were increased in six patients with chronic renal failure and hypertension uncontrolled by dialysis and hypotensive drugs. Lower and often normal levels were found in 10 patients whose blood pressure was controlled by dialysis treatment. For a variety of reasons all patients were subjected to bilateral nephrectomy. The logarithm of the decrease in plasma concentrations of renin and angiotensin II was significantly related to the fall of blood pressure after operation. Plasma renin concentration correlated significantly with blood angiotensin I concentration and with plasma angiotensin II in samples taken before and after nephrectomy. Renin, angiotensin I, and angiotensin II were measurable in samples of blood taken 48 hours or more after the operation.